Implementation of Website-Based Graduate Learning Outcomes Measurement System - Erdiansyah, Umri; Syahputra, Guntur; Rudi, Fachri Yanuar (Politeknik Negeri Lhokseumawe, 2025)
Digital transformation in higher education quality assurance has become imperative following the enactment of the Minister of Education, Culture, Research, and Technology Regulation No. 53 of 2023. This study proposes the development of a web-based Graduate Learning Outcomes (GLO) measurement system to accelerate academic evaluation effectiveness at Politeknik Negeri Lhokseumawe. Employing a Research and Development (RD) approach with the Waterfall development model, this research designs the system architecture using the Model-View-Controller (MVC) pattern to ensure application scalability and modularity. The system integrates academic data management features, automated GLO calculations, and analytical data visualization to support data-driven decision-making. System testing involved User Acceptance Testing (UAT), yielding a System Usability Scale (SUS) score of 82.3, indicating an 'excellent' user acceptance level. The results confirm that this platform not only meets national regulatory compliance standards but also enhances transparency and objectivity in graduate quality reporting. This implementation makes a strategic contribution to the modernization of institutional academic governance.